A retrospective study on anaemia of kidney diseases in cats presented to Universiti Veterinary Hospital, Universiti Putra Malaysia - Yeak, Lih Wen,
The kidneys play an important role in the clearance of toxic substances from the body and maintenance of health. The organs also maintain a constant extracellular environment to regulate metabolic processes. Kidney diseases can either be acute kidney injury (AKI) or chronic kidney disease (CKD). The objective of this retrospective study is to determine and compare the frequency and risk of development of anaemia in suspected AKI and CKD cases in cats. Records on feline kidney disease cases for year 2017 were obtained from the Haematology and Clinical Biochemistry Laboratory, Faculty of Veterinary Medicine, Universiti Putra Malaysia. The laboratory data was subjected to the International Renal Interest Society (IRIS) staging method to stage CKD in cats. The study shows that in 2017 there was higher frequency of anaemia in CKD than AKI cat patients. The data also showed cats in stage 3 CKD were not at risk of developing anaemia. However, at stage 4 CKD, cat patients were 18 times more at risk to develop anaemia than those at stage 1 or 2 CKD. In conclusion, cats in stage 4 CKD had the highest risk to develop anaemia all cats with CKD.